Safety and exploiting of crown pillars in Trepça stantërg mine - Gashi, Jahir; Zenel Sejfijaj (International Journal of Computational and Experimental Science and Engineering, 2025)
Most ore bodies of the Trepça deposit, Stantërg are known for a characteristic of these ore bodies with a slope angle and the formation of crown pillars and safety plates in the process of mining at the stopes, especially when the mineral body is of large size. The exploitation of these mineral bodies in existing stopes reaches the existing final levels of exploitation and in those cases when production capacities are in the limited phase, then in order to increase the quality of the ore in production, it is necessary to design the crown pillars and the method of their exploitation using productive mining machinery with a special focus on safety at work. Safety during the use of these plates is established according to the criteria and practices applied which have found proper implementation. The use of productive loading machines can significantly jeopardize this safety; therefore it is necessary to conduct an analysis that will determine the losses of ore in the working sites by implementing safety measures for the use of safety bearing plates. In order to leverage the maximum capacity of exploitation of this mass of mineral located in the bearing plate, the bottom-up ore body exploitation system has been applied. The mining of ore bodies in the lower levels such as the 10th and 11th levels has been carried out using modern machines with large productive capacities.